1983
DOI: 10.1111/j.1365-2125.1983.tb02258.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum alpha 1‐acid glycoprotein and the binding of drugs in obesity.

Abstract: Although clinically relevant, drug-protein interactions in the morbidly obese population have not been studied thoroughly. The objective of this study was to evaluate serum chemistry profiles and the degree of serum protein binding of propranolol, diazepam and phenytoin in the serum of four female, morbidly obese (> 190% of ideal body weight) and eight control female subjects. Serum triglyceride concentrations were higher and high-density lipoproteins were lower in the obese subjects than in the control group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
1
2

Year Published

1984
1984
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 19 publications
3
38
1
2
Order By: Relevance
“…Circulating ORM levels in our study group were more than twice the average levels reported in healthy people (Fournier et al, 2000). A previous study involving morbidly obese females and moderately obese males also showed that ORM protein concentrations were doubled compared to lean controls (Benedek et al, 1983;1984). We also showed previously that serum ORM levels were significantly elevated in obese people as compared to healthy people (Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…Circulating ORM levels in our study group were more than twice the average levels reported in healthy people (Fournier et al, 2000). A previous study involving morbidly obese females and moderately obese males also showed that ORM protein concentrations were doubled compared to lean controls (Benedek et al, 1983;1984). We also showed previously that serum ORM levels were significantly elevated in obese people as compared to healthy people (Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…In the ATV/RTV group, female participants had a higher median BMI than the male participants, and both participants with BMI >40 were female. In this analysis, RTV protein binding was shown to be sensitive to BMI, but not ATV or EFV; in the PK literature, the relationship between obesity and protein binding has not been clearly delineated, although it is postulated that alpha‐1 acid glycoprotein concentrations, to which RTV binds, are increased in obesity 43, 44, 45. This may also be a function of sex differences, as BMI and sex are linked, and our sample size is moderate.…”
Section: Discussionmentioning
confidence: 83%
“…Results from a previous study (Benedek et al, 1983) involving morbidly obese females showed that al-acid glycoprotein (AAG) concentrations were doubled as compared to lean female controls. This increase in serum AAG concentrations resulted in an increase in pro-pranolol protein binding in the morbidly obese *Address correspondence to P. J.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, altered physiology may result in altered drug disposition in the obese population. Drug-serum protein binding is an important determinant of drug disposition, which has only recently been addressed in the obese population (Benedek et al, 1983;Abernethy et al, 1981Abernethy et al, , 1982.…”
Section: Introductionmentioning
confidence: 99%